Case report: Giant cell tumor of bone in the mandible of a goat—diagnostics, surgical treatment, and outcome - Biermann, Nora M.; Piechl, Susanna; Dinhopl, Nora; Fuchs-Baumgartinger, Andrea; Weissenbacher-Lang, Christiane; Bertram, Christof A. (Frontiers in Veterinary Science, 2024)
Neoplastic processes of the mandible and their treatment are rarely reported in large animal species. Specifically, giant cell tumor of bone is an uncommon tumor in animals and has been associated in humans with locally invasive behavior and a high recurrence rate. En-bloc resection is the treatment of choice, but depending on the localization of the tumor, this may result in functional deficits. This report details the diagnostic work-up, treatment, and long-term outcome of a giant cell tumor of bone involving the rostral mandible and mandibular symphysis of a goat. Extensive rostral mandibulectomy involving the entire mandibular symphysis without surgical fixation of the hemimandibles was performed. Histological and electron microscopic findings of the tumor were consistent with a giant cell tumor of bone. Although a mutation of the H3F3A gene is considered the driver of tumor development in human giant cell tumors, using molecular analysis, this gene mutation could not be confirmed in this case. Follow-up examinations revealed spontaneous secondary fusion of both hemimandibles and no signs of tumor recurrence. Nearly 1 year after surgery, the owners reported no signs of tumor regrowth.